Surprising Pedagogy through Japanese Anime - drum, duskin (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2024)
At the intersection of embodiment, education, and anime, this essay describes how transcultural classroom encounters with anime can pollinate changes in ecological self-conceptions and thus embodiment. Using examples from teaching with anime in Russia and the United States, I describe how interpretive encounters shifted students’ ecological self-sense and conceptualization of embodiment. In the classroom, anime acted as an interpretive device for teaching contemporary thought about ecology, technology, microbes, animal-human figures, interconnection, and interdependence. I present evidence of oddly successful encounters between local Japanese cultural/embodied contexts of anime and its partial connections to globally shared human ecological and technological situations. In these transcultural encounters, the Japanese anime pollinate and germinate material and conceptual possibilities that are incipient for the students but not easily possibly with outside pollination.